Disrupted intra- and inter-network connectivity in unilateral acute tinnitus with hearing loss - Zhou, Gang-Ping; Li, Wang-Wei; Chen, Yu-Chen; Wei, Heng-Le; Yu, Yu-Sheng; Guo, Xi; Yin, Xindao; Tao, Yue-Jin; Zhang, Hong (Frontiers in Aging Neuroscience, 2022)
Purpose: Currently, the underlying neurophysiological mechanism of acute tinnitus. is still poorly understood. The present study aimed to explore differences of brain functional connectivity (FC) within and between resting state networks (RSNs) in acute tinnitus patients with hearing loss (ATHL). Further, the current study also evaluated the correlations between FC alterations and clinical characteristics. Methods: Two matched groups of 40 patients and 40 healthy controls (HCs) were included. Independent component analysis (ICA) was employed to obtain RSNs and FC differences were calculated within RSNs. In addition, the relationships between networks were conducted using functional network connectivity (FNC) analysis. Finally, analysis of correlation was used to evaluate the relationship between FNC abnormalities and clinical data. Results: Results of the current study found that seven major RSNs including the auditory network (AN), cerebellum network (CN), default mode network (DMN), executive control network (ECN), sensorimotor network (SMN), ventral attention network (VAN), and visual network (VN) were extracted using the group ICA in both groups. Further, it was noted that the ATHL group showed aberrant FC within the CN, ECN, and VN as compared with HCs. Moreover, different patterns of network interactions were observed between groups, including the SMN-ECN, SMN-CN, ECN-AN, DMN-VAN, and DMN-CN connections. The correlations between functional disconnection and clinical characteristics in ATHL were also found in the present study. Conclusion: In conclusion, the current study indicated widespread alterations of intra- and inter-network connectivity in ATHL, suggesting that multiple large-scale network dysfunctions and interactions are involved in the early stage. Furthermore, our findings may provide new perspectives to understand the neuropathophysiological mechanism in acute tinnitus. Keywords: Functional network connectivity, Independent component analysis, Resting-state fMRI, Acute tinnitus, Resting state network